Optimization of Bumi Lestari Maluku Waste Bank through the CSR Program of PT Pertamina Patra Niaga DPPU Pattimura: Optimalisasi Bank Sampah Bumi Lestari Maluku Melalui Program CSR PT Pertamina Patra Niaga DPPU Pattimura - Gracia Victoria Souisa; Lydia Laurencia; Vina Nur Azizah (Yayasan Ahmar Cendekia Indonesia, 2022)
Bumi Lestari Maluku Waste Bank (BLM) is a pilot waste bank in Ambon city with some problems such as the lack of knowledge in managing managerial and administrative functions, the lack of networks for selling collected waste, and the lack of product innovations in waste management. PT Pertamina Patra Niaga DPPU Pattimura conducts community empowerment for the BLM Waste Bank through a CSR program to create team with structured managerial and administrative functions, understand the eligible and on-demand products, and make eco-enzyme. The method of this empowerment project used socialization and joint practice. The empowerment results are an improvement in managerial and administrative functions; an increase in knowledge and skills of packaging; implementation of a circular economy through networking with industry; production of eco-enzyme. The conclusion is that the community empowerment project on BLM Waste Bank has provided knowledge and skills in managerial, administrative, and marketing aspects; and developed eco-enzyme products. Abstrak Bank Sampah Bumi Lestari Maluku (BLM) merupakan salah satu Bank Sampah percontohan di kota Ambon namun memiliki permasalahan seperti kurangnya pengetahuan pengurus terkait fungsi manajerial dan adminitratif, kurangnya jejaring dalam menjual sampah, dan kurangnya inovasi produk. PT Pertamina Patra Niaga DPPU Pattimura menjalankan kegiatan pemberdayaan masyarakat kepada Kelompok Bank Sampah BLM sebagai salah satu bentuk program CSR untuk membangun tim dalam fungsi manajerial dan administratif yang terstruktur, memberikan pemahaman terkait pengemasan produk yang layak dan diminati di pasaran, dan membuat inovasi eco-enzym. Metode yang digunakan adalah sosialisasi dan praktik bersama. Hasil pemberdayaan ini adalah adanya peningkatan fungsi manajerial dan administratif; peningkatan pengemasan produk; adanya penerapan dari ekonomi sirkular melalui jejaring industri; dan adanya produksi eco-enzym. Kesimpulan dari pemberdayaan masyarakat yang dilakukan pada kelompok Bank Sampah BLM telah memberikan pengetahuan dan meningkatkan kemampuan pengurus dalam fungsi manajerial, administratif, dan pemasaran (ekonomi sirkuler), serta dapat mengembangkan inovasi produk eco-enzym.